PENGARUH STORE ATMOSPHERE, DISPLAY PRODUK, PERSEPSI HARGA TERHADAP MINAT BELI KONSUMEN PADA CV IRAMA HOUSEWARE - Besty D. Pasaribu; Ananda Fitriani Dewi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This research aims to analyze the influence of Store Atmosphere, Product Display, and Price Perception on consumer Purchase Interest at CV. Rhythm Houseware. The research background is based on a decline in sales in the last three years as well as pre-survey results which show low consumer buying interest. This research uses a quantitative approach with survey methods. Data was obtained through distributing questionnaires to 100 respondents who were CV consumers. Rhythm Houseware. The analysis technique used is multiple linear regression using the SPSS program. The research results show that Store Atmosphere has a positive and significant effect on Purchase Interest, with a value of t = 4.235 > t table = 1.660 and a significant value of 0.000. Product Display has a positive and significant effect on Purchase Interest with a value of t = 2.168 > t table = 1.660 and is significant 0.033. Price perception has a positive and significant effect on buying interest with a value of tcount = 5.510 > ttable = 1.660 and a significant value of 0.000. Simultaneously, the three independent variables have a positive and significant effect on Purchase Interest with a value of F_count = 98,800 > F_table= 2.70 and a significant value of 0.000. The Adjusted R Square value of 0.748 indicates that 74.8% of the variation in Purchase Interest can be explained by the three variables, while the remaining 25.2% is influenced by other factors outside this research.